2009
DOI: 10.1002/tox.20476
|View full text |Cite
|
Sign up to set email alerts
|

Blood lead levels in children of Lucknow, India

Abstract: After implementing measures to control lead pollution in many countries, blood lead levels (BLLs) in children have been declined. The phase-out of leaded petrol began in Lucknow, the capital of most populated state, Uttar Pradesh in India on April 1, 2000. We evaluated the mean BLL and associated risk factors for lead exposure in Lucknow children (3-12 years) after petrol lead phase-out activity. The mean BLL of the 200 children was 9.3 microg/dL (range: 1.0-27.9 microg/dL). Seventy-four children (37%) had BLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 41 publications
(54 reference statements)
3
8
0
2
Order By: Relevance
“…Previous studies have demonstrated that concentrations of particulate matter and air pollutants are higher in areas closer to industrial facilities (Burstyn et al, 2007; Gildemeister et al, 2007). Therefore, our findings may support those of studies previously reporting associations between distance from point sources, duration and frequency of exposure to air pollutants, and subsequent higher body burden of toxicants for individuals living in those areas, including those reporting higher hair, urine, and blood levels of lead, mercury, and arsenic in those living closer to point sources such as agricultural land (Molina-Villalba et al, 2014), high-traffic roads (Ahamed et al, 2010; Gulson et al, 2006; Rahbar et al, 2002; Shen et al, 1997; Stroh et al, 2009), smelters (Do et al, 2011; Hegde et al, 2010; Hwang et al, 1997; Leroyer et al, 2000; Stroh et al, 2009), and mines (Basu et al, 2010; Wickre et al, 2004). Additionally, exposures to ambient air pollutants have been shown to stimulate oxidative stress and inflammation in humans, which may contribute to the pathogenesis of neurodevelopment and ASD.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have demonstrated that concentrations of particulate matter and air pollutants are higher in areas closer to industrial facilities (Burstyn et al, 2007; Gildemeister et al, 2007). Therefore, our findings may support those of studies previously reporting associations between distance from point sources, duration and frequency of exposure to air pollutants, and subsequent higher body burden of toxicants for individuals living in those areas, including those reporting higher hair, urine, and blood levels of lead, mercury, and arsenic in those living closer to point sources such as agricultural land (Molina-Villalba et al, 2014), high-traffic roads (Ahamed et al, 2010; Gulson et al, 2006; Rahbar et al, 2002; Shen et al, 1997; Stroh et al, 2009), smelters (Do et al, 2011; Hegde et al, 2010; Hwang et al, 1997; Leroyer et al, 2000; Stroh et al, 2009), and mines (Basu et al, 2010; Wickre et al, 2004). Additionally, exposures to ambient air pollutants have been shown to stimulate oxidative stress and inflammation in humans, which may contribute to the pathogenesis of neurodevelopment and ASD.…”
Section: Discussionsupporting
confidence: 89%
“…For example, Volk et al (2011) reported a positive association with ASD case-status and birth residence near freeways, which may also be a proxy for exposure to lead sources (Ahamed et al, 2010; Gulson et al, 2006; Rahbar et al, 2002; Stroh et al, 2009). Notably, Palmer et al (2009) also reported an association with school system-based ASD prevalence, according to school records, and proximity of school districts to mercury emitting industrial facilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is also much higher than the BLLs means in urban areas in Canada (children aged 6-11 years, 10.2 μg/l) and in Brazil (children aged 6-8 years, 24 μg/l) [30,34]. The BLLs in our series are however comparable to other studies in children exposed to roads with heavy traffic, e.g., studies conducted in India (children aged 3-12 years) and in Uruguay (children aged 2-14 years) cities reported BLLs of 93.2 μg/l and 94 μg/l, respectively [35,36]. Interestingly, these studies reported the proximity to traffic as the main determinant of high BLLs in children.…”
Section: Ijomeh 2014;27(4)supporting
confidence: 86%
“…While the persistence of the observed relationship between BPb concentrations at 2 years of age and cognitive ability deserves further study, the neurotoxic effects of Pb are well documented and efforts should be made to reduce or eliminate childhood Pb exposures. Childhood BPb concentrations have declined in the United States (US), but childhood Pb exposure remains a persistent problem in developing countries (Ahamed et al, 2010; He et al, 2009; Roy et al, 2009; Shi et al, 2010; Zhang et al, 2009). If specific periods of development are found to be sensitive to Pb, then public health interventions could be better targeted to reduce or eliminate exposures prior to susceptible developmental windows.…”
Section: Discussionmentioning
confidence: 99%